Temporal Adverbs as Connectives with Consecutive Nuance in Ancient Greek - Jiménez Delgado, José Miguel (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
The aim of this paper is to identify the temporal adverbs that are used as connectives with consecutive nuance in Ancient Greek and to ascertain their peculiarities in that use. The searched corpus are the works by Herodotus, Thucydides, Xenophon and Polybius. We can conclude from our data that the temporal adverbs used as connectives with consecutive nuance in Ancient Greek are those expressing sequentiality and that the evolution of some of them into illative conjunctions is at its beginning.
Keywords: temporal adverbs; inferential connectors; conjunctive adverbs; discourse markers.